Two new Atlantic Forest Myrtaceae from Brazil - Bunger, Mariana De Oliveira; Stehmann, João Renato; Sobral, Marcos (Phytotaxa, 2013)
Two new Brazilian species of Eugenia are described and illustrated, Eugenia regia and  E. espinhacensis. Eugenia regia, collected in coastal Atlantic rainforests in the southeastern states of São Paulo and Rio de Janeiro, is related to E. bunchosiifolia, from which it differs by its larger leaves, flowers and trichomes. Eugenia espinhacensis was collected in seasonal Atlantic forests of the state of Minas Gerais; it is similar to E. bocainensis, from wich can be distinguished by its obtuse sepals and pilose branches, pedicels and flowers. São descritas e ilustradas duas novas espécies de Eugenia: Eugenia regia e E. espinhacensis. A primeira encontrada nas matas ombrófilas costeiras do litoral norte de São Paulo e sul do Rio de Janeiro tem sido frequentemente e erroneamente nomeada sob E. bunchosiifolia, da qual difere-se pelo discrepante tamanho das folhas, flores e pilosidade. E. espinhacensis é uma espécie ocorrente nas matas semidecíduas do Quadrilátero Ferrífero, em Minas Gerais, numa região altamente explorada pela extração de minério de ferro.  Esta assemelha-se a E. bocainensis, porém difere-se pelas sépalas obtusas e pilosidade dos pedicelos, sépalas e ramos.